Occupational health and safety provision awareness among construction workers on the construction industry of Windhoek, Namibia - Nghitanwa, Emma Maano; Zungu, Lindiwe I (International Journal of Health, 2017)
The purpose of this study is to discuss the awareness on the provision of occupational health and safety (OHS) among construction workers in the construction industry of Windhoek, Namibia. A quantitative, descriptive, cross sectional design was applied. Interviewer- led questionnaires were used to collect the data among 549 participants. The study results showed that most construction workers express poor awareness on construction industry OHS provision. The interventions such as OHS training enforcement is needed in order to increase construction workers OHS awareness through training. The employees need to establish OHS programs on the construction sites which include the development of the OHS policies which shows organisation commitment towards occupational health and safety of its workers.